2016
DOI: 10.1074/jbc.m116.752303
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal growth factor receptor 4 (Her4) Suppresses p53 Protein via Targeting the MDMX-MDM2 Protein Complex

Abstract: Edited by Eric FearonDeregulated receptor tyrosine kinase (RTK) signaling is frequently associated with tumorigenesis and therapy resistance, but its underlying mechanisms still need to be elucidated. In this study, we have shown that the RTK human epidermal growth factor receptor 4 (Her4, also known as Erbb4) can inhibit the tumor suppressor p53 by regulating MDMX-mouse double minute 2 homolog (MDM2) complex stability. Upon activation by either overexpression of a constitutively active vector or ligand bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Furthermore, we confirmed that HRG but not EGF decreases p53 expression ( Figures 2H, 2I, and S5A-S5D) through a similar mechanism involving the MDM2-MDMX axis (Gerarduzzi et al, 2016; data not shown), again suggesting that MAPK dynamics is crucial to establish a balance between cell-cycle arrest and progression in a p53-dependent manner. The p53 levels could be rescued by treating the cells with U0126 in the presence of HRG and DNA damage ( Figures S5E and S5F).…”
Section: Erk Temporal Dynamics Dictates G2 Checkpoint Enforcementsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, we confirmed that HRG but not EGF decreases p53 expression ( Figures 2H, 2I, and S5A-S5D) through a similar mechanism involving the MDM2-MDMX axis (Gerarduzzi et al, 2016; data not shown), again suggesting that MAPK dynamics is crucial to establish a balance between cell-cycle arrest and progression in a p53-dependent manner. The p53 levels could be rescued by treating the cells with U0126 in the presence of HRG and DNA damage ( Figures S5E and S5F).…”
Section: Erk Temporal Dynamics Dictates G2 Checkpoint Enforcementsupporting
confidence: 69%
“…The abrogation of MAPK signaling enhances checkpoint stringency, whereas its sustained stimulation with HRG or light-inducible RAF increases checkpoint negligence. Mechanistically, sustained MAPK signaling during checkpoint activation results in the Lahav et al (2004), subsequently modeled with the addition of the WIP1 phosphatase role in Batchelor et al (2011), where ERK activity discovered in this work is exemplified with the reported MAPK-MDM2 interaction (Gerarduzzi et al, 2016). (C) A simple competitive model for the DNA damage checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…We show that the complexes of CDK4 and Cyclin D1 on the one hand, and MDM2 and p53 on the other hand, associate with each other. These findings are in line with a previous report that MDMX, another close binding partner of MDM2 and p53, is phosphorylated by CDK4 37 . According to this report, CDK4-mediated phosphorylation of MDMX stabilizes its interaction with MDM2 to antagonize p53.…”
Section: Discussionsupporting
confidence: 93%
“…Phosphorylation of MDMX on Ser314 was able to favor MDMX nuclear import and increase its stability by protecting it from MDM2-mediated degradation (12,13). The identification of the Ser314 site as a target of multiple tyrosine kinases signaling point at a role of MDMX as the converging point, or “hub”, of oncogenic signaling aimed at suppressing p53, given the prosurvival role of tyrosine kinases in cancer development and the fact that p53 functional deactivation is required for tumorigenesis.…”
Section: The Identified Phosphorylation Sites In Mdmx (Table 1)mentioning
confidence: 99%
“…We propose that MDMX represents a “signaling hub” transducing mitogenic signals as well as stress signals to the MDMX-MDM2 complex and therefore to p53. In a cancer context, our lab has shown that at least two receptor tyrosine kinases can inhibit p53 activation via modulation of the MDMX-MDM2 complex stability and, specifically, through post-translational modifications of MDMX (12,13). These and other studies (14) suggest that MDMX could be a promising and rather safe therapeutic target for pharmacological restoration of p53 in tumors harboring wild-type p53.…”
Section: Introductionmentioning
confidence: 99%